A study on the validity of the shortened form of the Minnesota Counseling Inventory (MCI) in Turkish - Özdemir, Neylan Pektaş. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 1985., 1985)
The purpose of the present study was to obtain information on the validity of the shorthened form of the Minnesota Counseling Inventory (MCI) adapted in Turkey. The MCI is an inventory which gives information about the personality structure and problems of American. adolescents. It was developed by Berdie and Layton (1957). The Turkish adaptation of the shorthened form of Mel in Turkey was accomplished by Akdag (1979). It has eight sub-scales which are Validity (V) Social Relationships (SR), Family Relationships (FR), Emotional Stability (ES), Conformity (C), Adjustment to Reality (R), Mood (M) and Leadership (L) scales. In the validation of these scales, teacher nominations, evaluations of the family and the Si scale of the MMPI were used as criterion measures. "Student Evaluation Forms" were developed for family evaluations and teacher nominations. Two "Student Evaluation Forms for Teachers" were established for each of the six scales including the SR, ES, C, R, M and L scales, one containing the descriptions of the negative characteristics of the particular scale, the other the positive characteristics. Using these descriptions, teachers prepared lists of nominations from which two groups (positively negatively nominated) of students were formed for each scale. The scores of the negatively and positively nominated groups were compared with each other as well as with an independent normal sample obtained from the Education Department of the Bogaziçi University. In the validation of the FR scale, "Student Evaluation Forms for Family" were developed and scores of this form were correlated with the scores of the FR scale. Correspondance between teacher nominations and student scores on SR, ES, C, R, M and L scales were also investigated and the appropriatness of the scale means in discriminating students was tested. Additionally the SR scale was compared with the si scale of the MMPI whose validity on the Turkish samples is established. Findings of this study indicated that the SR, ES, L, R and C scales effectively discriminated between the students of low and high characteristics on these traits. The SR, ES, C, Rand L scales were particularly effective in discriminating the students with poor adjustment characteristics while only the SR and ES scales were effective in discriminating the students w~th poor adjustment characteristics from the normals. The mean scores of four of the scales were found appropriate as critical scores, but not those of the M and R scales. Additional analysis on the SR scale also showed that it measures more or less the same behavior characteristics as the Si scale of the MMPI. Lack of data on the validity/reliability of the teacher ratings and family evaluation forms including a well administered systematic teacher training for accurate observations constitute a limitation of this study. The other important limitation is related to sampling. Only the ninth graders in a highly selective private high school were included in this study. Cross-Validation and use of different criterion measures were recommended for further research.
Keywords: Educational tests and measurements.; Educational counseling.